Becoming a Media-Oriented Gen Z Using Information Technology - Susi Widyastuti; Muhammad Erwanto; Kosim; Ilman Kadori; Faisal Akbar; Igen mayesha; Virgiyanti (PT. Berkah Digital Teknologi, 2024)
This community service program aims to empower Generation Z students at the MODERN IIBS EL-'AZAM Islamic Boarding School to become agents of change oriented towards community service by utilizing information technology. Through the program, students experienced increased digital literacy, communication skills, and social awareness. They were able to design and implement technology-based community service projects that generated positive impacts for the surrounding community. The community expressed appreciation for the programs implemented and hoped that similar initiatives could be sustained. These findings indicate that empowering Generation Z in Islamic boarding schools through the utilization of information technology can be an effective solution to improve community engagement and service. The program not only benefited the students, but also addressed real needs identified in the local community, demonstrating the potential for technology-driven community service to create lasting change. ABSTRAK Program pengabdian masyarakat ini bertujuan untuk memberdayakan santri Generasi Z di Pondok Pesantren MODERN IIBS EL-'AZAM untuk menjadi agen perubahan yang berorientasi pada pengabdian kepada masyarakat dengan memanfaatkan teknologi informasi. Melalui program ini, santri mengalami peningkatan literasi digital, keterampilan berkomunikasi, dan kepedulian sosial. Mereka mampu merancang dan melaksanakan proyek pengabdian kepada masyarakat berbasis teknologi yang memberikan dampak positif bagi masyarakat sekitar. Masyarakat menyampaikan apresiasi atas program yang dilaksanakan dan berharap agar kegiatan serupa dapat berkelanjutan. Temuan ini menunjukkan bahwa pemberdayaan Generasi Z di pondok pesantren melalui pemanfaatan teknologi informasi dapat menjadi solusi efektif untuk meningkatkan keterlibatan dan pengabdian kepada masyarakat. Program ini tidak hanya bermanfaat bagi santri, tetapi juga menjawab kebutuhan nyata yang teridentifikasi di masyarakat setempat, menunjukkan potensi pengabdian kepada masyarakat berbasis teknologi untuk menciptakan perubahan yang berkelanjutan.